BH4 deficiency identified in a neonatal screening program for hyperphenylalaninemia - Cezar Antonio Abreu de Souza; Michelle Rosa Andrade Alves; Rosangelis del Lama Soares; Viviane de Cássia Kanufre; Valéria de Melo Rodrigues; Rocksane de Carvalho Norton; Ana Lúcia Pimenta Starling; Marcos José Burle de Aguiar (Brazilian Society of Pediatrics, 2018)
Objectives: To show the general prevalence and to characterize tetrahydrobiopterin (BH4) deficiencies with hyperphenylalaninemia, identified by the Neonatal Screening Program of the State of Minas Gerais. Methods: Descriptive study of patients with BH4 deficiency identified by the Neonatal Screening Program of the State of Minas Gerais. Results: The prevalence found was 2.1 for 1,000,000 live births, with a frequency of 1.71% among hyperphenylalaninemias. There were four cases (40%) with 6-pyruvoyl-tetrahydropterin synthase deficiency, three with GTP cyclohydrolase I - autosomal recessive form deficiency, and three with dihydropteridine reductase deficiency (30% each). Six patients were diagnosed due to clinical suspicion and four cases due to systematic screening in neonatal screening. After the start of the treatment, patients identified by neonatal screening had rapid improvement and improved neuropsychomotor development compared to those diagnosed by the medical history. Conclusions: The prevalence of BH4 deficiencies in Minas Gerais was slightly higher than that found in the literature, but the frequency among hyperphenylalaninemias was similar. Although rare, they are severe diseases and, if left untreated, lead to developmental delays, abnormal movements, seizures, and premature death. Early treatment onset (starting before 5 months of age) showed good results in preventing intellectual disability, justifying the screening of these deficiencies in newborns with hyperphenylalaninemia identified at the neonatal screening programs for phenylketonuria.